2021
DOI: 10.1021/acsami.0c19665
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscratch-Directed Self-Assembly of Block Copolymer Thin Films

Abstract: Directed self-assembly (DSA) of block copolymer (BCP) thin films is of particular interest in nanoscience and nanotechnology due to its superior ability to form various well-aligned nanopatterns. Herein, nanoscratch-DSA is introduced as a simple and scalable DSA strategy allowing highly aligned BCP nanopatterns over a large area. A gentle scratching on the target substrate with a commercial diamond lapping film can form uniaxially aligned nanoscratches. As applied in BCP thin films, the nanoscratch effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Directed self-assembly (DSA) integrates "top-down" and "bottom-up" approaches for producing highly aligned nanopatterns by utilizing prepatterned substrates to guide microdomain formation of BCP thin films as shown in (Figure 9). [291][292][293][294][295][296] As this is one of the most well-developed fields in BCP nanostructure alignment, a number of excellent reviews already have comprehensive discussion focusing on this area. [105,160,163] Here, we will only succinctly discuss the physical (graphoepitaxy) and chemical (chemoepitaxy) patterning of substrates to induce nanostructural alignment in BCP systems.…”
Section: Directed Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Directed self-assembly (DSA) integrates "top-down" and "bottom-up" approaches for producing highly aligned nanopatterns by utilizing prepatterned substrates to guide microdomain formation of BCP thin films as shown in (Figure 9). [291][292][293][294][295][296] As this is one of the most well-developed fields in BCP nanostructure alignment, a number of excellent reviews already have comprehensive discussion focusing on this area. [105,160,163] Here, we will only succinctly discuss the physical (graphoepitaxy) and chemical (chemoepitaxy) patterning of substrates to induce nanostructural alignment in BCP systems.…”
Section: Directed Self-assemblymentioning
confidence: 99%
“…[443] Since then, numerous research works about BCP lithography have been reported over the past decades with the aim to provide alternative and promising patterning technologies to complement conventional optical lithography, highlighted by several excellent reviews. [28,[291][292][293][294][295][444][445][446][447][448] In a typical nanolithography process using BCPs as templates, a BCP thin film is first aligned to obtain patterned nanofeatures using various annealing strategies as described in the previous section. Subsequently, these nanopatterns can be replicated on a solid substrate by a variety of pattern transfer methods, including dry etching, wet etching, and ion beam etching.…”
Section: Nanolithography For Microelectronics Fabricationmentioning
confidence: 99%
“…Thus, additional processing is required to increase in‐plane orientation and to increase the domain sizes of the BCP nanostructures, for example, the directed self‐assembly (DSA) method. [ 10–17 ] To produce nanopatterns in a large area with controlled orientation, multiple shearing methods [ 18 ] have been introduced employing cold zone annealing, [ 19 ] laser annealing, [ 20,21 ] or roller‐shearing. [ 22,23 ] However, these methods are not effective to generate and control the out‐of‐plane domain orientation, especially for the BCPs having a high Flory–Huggins interaction parameter (χ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, additional processing is required to increase in-plane orientation and to increase the domain sizes of the BCP nanostructures, for example, the directed self-assembly (DSA) method. [10][11][12][13][14][15][16][17] To produce nanopatterns in a large area with controlled orientation, multiple shearing methods [18] have been introduced controlling the out-of-plane domain orientation becomes challenging and fails for the sub-20-nm BCP nanopatterning.…”
Section: Introductionmentioning
confidence: 99%
“…BCPs composed of two or more incompatible segments can obtain excellent properties of each segment orthogonally by self-assembling to form various ordered nanostructures, including spheres, hexagonally packed cylinders (HEX), lamellae (LAM), the gyroid network phase (GYR), and the Fddd network phase (O 70 ). However, many properties of BCPs, including the modulus and conductivity, are usually affected by the long-range order of nanostructures. Fortunately, thin-film assembly of BCPs provides a fascinating approach for preparing thin films with long-range ordered nanostructures. In the past decades, various strategies, including magnetic field, electric field, graphoepitaxy, solvent vapor annealing, ,, and supramolecular cooperative motions (SMCMs), , have been explored to control the orientation of nanostructures in BCP thin films.…”
Section: Introductionmentioning
confidence: 99%